Ethics and epics : reflections on Indian ethos - Pandey, K.C. (New Delhi Readworthy Publications, 2011)
Study on Swarnajayanti Gram Swarozgar Yojana in Jalpaiguri District of West Bengal, India.
Includes index
Contributed articles